A atuação da igreja católica junto ao adolescente em conflito com a lei: a pastoral do menor e o programa liberdade assistida comunitária - Barros Filho, Alberto dos Santos (2012)
This research deals with the execution of the socio-educational procedure for assisted conditional release of minors according to the Child and Adolescent By-laws. This measure is one of the sanctions applied to adolescents who have broken the law. The empirical field under analysis was the Assisted Conditional Release Community Program (LAC) developed by the Catholic Church’s organization Pastoral do Menor (PANEM) in the city of Fortaleza, State of Ceara, Brazil. The aim was to identify and evaluate configurations and meanings of that kind of action within a certain area of the Catholic Church; what were the practices and perceptions undertaken by the PAMEN’s agents, mainly by professionals from LAC; how this has an effect on the action and the kind of politics offered to targeted adolescents and other young people by the Program; and what is the role of the government in face of those relations and perceptions. This research has, therefore, an interface with the so-called areas covered by Public Policies for Infancy, Adolescence and Youth as well as Social Policies from the Catholic Church. Both institutions, government and Catholic Church, have their own rules and procedures and are influenced by several political and ideological disputes from which arise conflicts, tensions and negotiations related to the kind of discourse and actions to be adopted. Within this configuration one is to center attention upon the symbolic struggles (Bourdieu, 2003, 2005, 2008) that present hierarchies and connections involving the several agents and institutions in relation to the treatment given or that should be given to the these adolescents in their trajectories.